Effect of Chinese herbal medicine on sexual characteristics of females with precocious puberty: a meta-analysis - Wang, Ming; Zhao, Rui; Wang, Jing (Frontiers in Pharmacology, 2025)
BackgroundPrecocious puberty (PP) in girls is a growing concern globally, characterized by the early onset of sexual characteristics. Chinese Herbal Medicine (CHM) has been proposed as a therapeutic intervention. This meta-analysis evaluates the effects of CHM on primary and secondary sexual characteristics in females with precocious puberty.MethodsA comprehensive literature search was conducted in Medline, Web of Science, Scopus, China National Knowledge Infrastructure Chinese Biomedical Literature Database (CBM), and Wan-fang database for clinical studies evaluating CHM in girls with precocious puberty. Key outcomes analyzed were primary and secondary sexual traits, including the uterine and ovarian volume and breast nucleus diameter. Data was pooled using a random-effects model and expressed as Standardized Mean Differences (SMD) with 95% confidence intervals.ResultsTwenty-five studies involving 2096 patients were included. CHM significantly decreased breast nucleus diameter (SMD = −1.48, 95% CI [−2.04, −0.92]), reduced uterine volume (SMD = −0.75, 95% CI [−1.24, −0.27]), ovarian volume (SMD = −0.63, 95% CI [−0.97, −0.30]), and follicular volume (SMD = −0.87, 95% CI [-1.49, −0.26]). Subgroup analysis showed the integration of CHM and GnRHa resulted in a notable decrease in the development of sexual traits when compared to GnRHa alone. There was no significant difference between CHM and GnRHa in treating sexual traits. Sensitivity analysis was conducted to address the source of heterogeneity.ConclusionCHM appears to effectively modulate primary sexual characteristics in females with precocious puberty. The findings of this study suggest that CHM is a good choice for adjuvant therapy along with GnRHa and also may serve as a complementary treatment for patients with PP.